System Approach as Methodological Basis of a Public Policy Study in the Field of Counteraction to Stigma and Discrimination of Patients With HIV/AIDS - Datsyuk, Viktoriya (Pressing Problems of Public Administration, 2019)
The article considers the role of the system approach as a methodological basis for the study of mechanisms of functioning of public policy in the  eld of counteraction to stigma and discrimination of patients with HIV/AIDS. It is shown that the use of systematic approach in conducting study allows us to consider public policy in the  eld of counteraction to stigmatization and discrimination of HIV-infected persons as a holistic system object with certain properties consisting of many elements. In this case, the components of this system are public policy instruments, stigma and discrimination, HIV-infected people, means of counteraction to stigmatization and discrimination. There are established relationships and subordination of these components. It is proved that the use of systematic approach is a prerequisite and a key link in conducting study to  nd out mechanisms for the functioning of public policy in the  eld of counteraction to stigma and discrimination of patients with HIV/AIDS.